1994
DOI: 10.1073/pnas.91.26.13038
|View full text |Cite
|
Sign up to set email alerts
|

Fourier-transform infrared spectroscopy and gas chromatography-mass spectrometry reveal a remarkable degree of structural damage in the DNA of wild fish exposed to toxic chemicals.

Abstract: The use of gas chromatography-mass spectrometry with selected ion monitoring (GC-MS/SIM) and Fourier-transform infrared (FT-IR) spectroscopy revealed a remarkable degree of damage in the hepatic DNA of fish exposed to toxic environmental chemicals, compared with controls. The exposed fish, which were neoplasm-free, were part of a population with a high incidence of liver cancer. GC-MS/SIM showed markedly high concentrations of hydroxyl radical-induced ring-opening products (e.g., 2,6-diamino-4-hydroxy-5-formam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…A similar study of feral English sole also found that fish from sites contaminated with PAHs and PCBs showed a high degree of hepatic DNA damage in the form of 8-OH adducts of guanine and adenine as well as FapyGua (125). These studies on lipid peroxidation and oxidative DNA damage demonstrate that mammals and fish exhibit similar lesions and that the markers used to detect toxic consequences of oxidative stress in mammalian systems are also useful in piscine models.…”
Section: As With Lipid Peroxidation Oxidative Damage To Dna Has Recementioning
confidence: 75%
“…A similar study of feral English sole also found that fish from sites contaminated with PAHs and PCBs showed a high degree of hepatic DNA damage in the form of 8-OH adducts of guanine and adenine as well as FapyGua (125). These studies on lipid peroxidation and oxidative DNA damage demonstrate that mammals and fish exhibit similar lesions and that the markers used to detect toxic consequences of oxidative stress in mammalian systems are also useful in piscine models.…”
Section: As With Lipid Peroxidation Oxidative Damage To Dna Has Recementioning
confidence: 75%
“…For example, nucleic acids are known to be targets for oxidative attack resulting in mutagenic structures: 4 the reactive OH x in icted damage in spectral areas assigned to NH vibrations of nucleotide bases (between 1700 and 1350 cm 21 ) and CO vibrations of deoxyribose. 24,25 Thus, the increased intensity around 1545 cm 2 1 and the decreased intensity at 1150 cm 2 1 could be due to substantial m odi cations in DNA structures, i.e., to the NH group vibrations of nucleotides and to the nearly degenerate stretching vibrations of the CO group of deoxyribose.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies prove that principles modified in DNA may be later one of the factors determining cancer metastases [48].…”
Section: S T R E S S O X I D At I V E S T R E S S a N D N E O P L A S T I C D I S E A S Ementioning
confidence: 99%